HUBUNGAN BUDAYA LITERASI DENGAN MINAT BACA SISWA DI KELAS IV SDN 64 SINGKAWANG - Handayani, Esti; Sulistri, Emi; Utama, Erdi Guna (Jurnal Elementary:Kajian Teori dan Hasil Penelitian Pendidikan Sekolah Dasar, 2024)
This study aims to describe the Relationship between Literacy Culture and Reading Interest in Class IV Students at SDN 64 Singkawang. This type of research is correlation research with a quantitative approach. The population and the sample used in this study was all fourth-grade students at SDN 64 Singkawang, totaling 30 students with using the saturated sampling technique. Then the data is analyzed by correlation Pearson product moment. The results showed: 1) Literacy culture at SDN 64 Singkawang averaged 84.28 so it was included in the good criteria; 2) Interest in reading at SDN 64 Singkawang averaged 72.29 so it was included in the sufficient criteria; 3) there is a relationship between literacy culture and reading interest of fourth-grade students at SDN 64 Singkawang about 32.49%.